An Empirical Study on the Determinants of Electronic Payment System - Ajitha ANGUSAMY; Jayanty KUPPUSAMY; Kavitha BALAKRISHNAN; Adeline Chow Mei YIN (Communications of International Proceedings, 2020)
The world is rapidly changing and becoming even advanced with the existence of technologies. One of the major changes is the evolvement of traditional payment methods to electronic payment systems (EPS). EPS, which was accepted globally when e-commerce was introduced, has provided many benefits to its users. Individual’s life has been enhanced as EPS provides ease in payment and is less-time consuming. Irrespective of innovations in e-payment methods, studies reveal that e-payment usage rate is lower in developing countries. Among the existing literature, very few studies focus on the consumers’ point of view. In this paper, a research model is proposed to examine the effect of transaction procedures, technical protection and usability of EPS on the perceived security and perceived trust of EPS, and also the effect of perceived security and perceived trust on the usage of EPS is studied. The model is evaluated empirically and the findings reveal that transaction procedures, technical protection and usability of EPS have a significant impact on the perceived security and perceived trust of EPS. Perceived security and perceived trust of EPS are found to be significant factors of EPS usage. The study is useful for companies and businesses that would like to enhance their payment system through electronic transactions. Findings suggest that managers should focus on providing the best in transaction procedures, technical protections and usability in order to enhance the perceived security and perceived trust EPS, which in turn will have a positive impact on the EPS usage.
Keywords: Perceived security; Perceived trust; Transaction; EPS; Usage.